Use of articles in Malaysian secondary school English language textbooks - Leong, Amelia Chiew Har (2012)
The English grammar articles are said to be the most difficult and the latest grammatical items to be acquired by the learners although articles are commonly used aspects of grammar in the English language. The problem with the article system is also faced by Malaysian English as Second Language (ESL) learners. Although all the three articles should be taught throughout the five years in the secondary schools in Malaysia as outlined in the Malaysian Curriculum Specification for English Language, learners are found to be still committing errors in using the articles. Due to this, the present study aims to investigate the use of the articles in the Malaysian Form One to Form Five English Language textbooks as textbooks are the core material used in the classroom to aid the teaching and learning process. This thesis analyses the distribution patterns of the articles, the distribution patterns of the word classes that colligate with the articles and the way the articles are presented in the five Malaysian Secondary School English Language textbooks. For this purpose, content analysis is employed and WordSmith Tools 4.0 is used to analyze the articles in the Malaysian Form One to Form Five English Language textbooks. Through the analyses of wordlists, and concordance lines, the distribution patterns and the way of presentation of the articles were obtained. The findings indicated that the article the is the most frequently occurring among the three articles, followed by the article a and lastly the article an. This result is similar to the frequency ranking of the articles in the British National Corpus (BNC) and Longman Grammar of Spoken and Written English (LGSWE). The findings also displayed that out of the 15 colligation patterns of the articles, there is only one colligation pattern that did not occur in all the five Malaysian Form One to Form Five English Language textbooks which is the colligation pattern of the article a with the words spelled with a vowel but pronounced with a consonant sound. The study also revealed that in the sections presenting the articles in the textbooks, the explicit explanations and input on the article usages before the article exercises are insufficient. There is also a lack of variety in the exercises on articles; most of the exercises are in the form of cloze passages. Although there are many article usages, only certain usages of article are put into emphasis in the textbooks, others are neglected. This study also uncovered that although not all the colligation patterns occurred in the textbooks but all of the colligation patterns were indirectly illustrated in between the blanks in the articles exercises. Hence, the findings portrayed the strengths and weaknesses of our Malaysian Secondary School English Language textbooks in terms of the English grammar articles. The findings of this study will expectedly provide the teachers with the knowledge on the articles occurrences and the teaching of articles in the textbooks. They can help the teachers to prepare efficient lesson plans for teaching articles in the ESL classrooms.